Evaluation of the MOSkin dosimeter for diagnostic X-ray CT beams. (April 2019) - Mendes Pereira, L.; Khoury, H.J.; Andrade, M.E.A.; Barros, V.S.M.; Cutajar, D.; Rosenfeld, A.B.
Highlights: The MO Skin dosimeter was characterized for X-ray diagnostic CT beams. The system was tested in a metrology laboratory and in clinical conditions. The MO Skin demonstrated potential for applications in CT dosimetry. Abstract: The aim of the present study was to evaluate the response of the MO Skin MOSFET dosimeter for X-ray diagnostic CT beams. Experiments were performed to investigate the sensitivity, energy dependence, reproducibility, fading and angular dependence of the dose response for the device. The dosimeter's performance was evaluated for the standard radiation qualities RQT 8, RQT 9 and RQT 10 in a metrology laboratory. In a CT scanner, the MO Skin was used to assess the air kerma profile and the dose profile in a phantom. The integral of the dose profile was compared to the CPMMA, 100 measured with a pencil ionization chamber. The results showed that the MO Skin response was linear and reproducible with doses in the CT range. Energy dependence varied up to a factor of 1.19 among the tested X-ray energies. Angular dependence of the response was not greater than 7.8% within the angle range from 0 to 90 degrees. Signal fading within 3 min was negligible. Additionally, the MO Skin was able to accurately assess the air kerma profile and the integral of the dose profile in a CT scanner. The integral of the dose profile in a phantom was in agreement with the CPMMA, 100 . The presented results demonstrated the potential of the MO Skin for application in CT dosimetry.